Sperm storage structures in the ovary of Helicolenus dactylopterus dactylopterus (Teleostei : Scorpaenidae): An ultrastructural study - Munoz, M.; Casadevall, M.; Bonet, S.; Quagio-Grassiotto, I (Kluwer Academic Publ, 2000)
The ultrastructure of ovarian sperm storage of Helicolenus dactylopterus dactylopterus is described, before and after the spawning period. The spermatozoa remain inside cryptal structures that are situated in the interlamellar gaps and are connected to the ovarian lumen by a duct. This complex forms a highly specialised structure. During the long storage period, crypts are richly vascularised. Their surrounding simple epithelia have intercellular junctions that may serve to protect the spermatozoa from the female immune system. At the moment during which insemination of mature oocytes occurs, the sperm may be expelled from cryptal structures by means of a spasmodic contraction. During the post spawning period, residual spermatozoa that remain in the crypts are eliminated by cryptal phagocytes. At the end of the process the crypts contain only an amorphous material.
Keywords: rockfish; internal fertilisation; spermatozoa maintenance